Estudio Avifaunístico en el Bosque Protector Umbría de la Parroquia el Chaupi del Cantón Mejía Provincia de Pichincha - Caizaluisa Sulca, Karen Giovanna (2019)
In the present investigation there was analyzed the abundance and the diversity of the avifauna in the Protective Forest Shady of the Parish Chaupi, Canton Mejia, by means of the implementation of temporary observatories, feeding-places and drinking-troughs, and the application of methods as the direct observation, the count for point and the photographic record they gave like proved a record of 26 species, 6 orders and 12 families: which are distributed in four zones of study, the same ones that decided by means of the vegetable(plant) abundance and altitude, in the Zone 1 (Remaining(Surplus) Forest) and the Zone 4 (Area of camping and gardens) registered 29 % of abundance of individuals registered respectively, in the zone 2 (Path of the Protective Forest Shady) 25 % of individuals was registered and in the zone 3 ( Viewing-point of the Protective Forest Shady) one registered 17 % of individuals, predominating over the Order Passeriforme, with the information of this investigation(research) a field guide was elaborated where information was included as the order, family, kind, species, common, scientific name and Englishman, also a general description was realized of each one of the registered species. By means of this guide of field of birds, the users have in their hands an extensive knowledge on the birds of the sector before mentioned. The present guide will consist with 26 sheets to color with images of high resolution this way to facilitate his use, in addition it will help to wake the interest of the visitors up to develop this activity faunístic in the sector. This guide of birds also was created by the purpose of generating knowledge Of each of the species that shape this forest, this is important since on having detailed the type of species that live this forest it is possible to give a better managing to each of the zones of study, and hereby could be preserved and preserved, this guide of birds tries to be a contribution for the development Shady Aviturístico of the Protective Forest and also for the parish to that it belongs, where it will be able to serve as direct and indirect sustenance to generate more tourist abundance to the place, doing of this one the worthy and only destination to be visited.